Tax Knowledge, Tax Enforcement Efforts, and Tax Compliance among Agribusinesses in Tagum City - Flores, Joe Mari N.; Barbosa, Honey Mae J.; Galo, Christine Mae G.; Paig, Princess Claire G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The main objective of this study is to identify the relationship between tax knowledge and tax enforcement efforts towards tax compliance of agri-business owners in Tagum City that could benefit the Agri-business owners, BIR, LGUs, Department of Agriculture (DA), and future researchers. The sample size of 259 was determined using the Slovin formula, and respondents were identified through simple random sampling. The results of this study are based on the data gathered from respondents who are managers, owners, or accounting staff of a registered agri-business through the dissemination of an adopted questionnaire authored by Twum et al. (2020) and Oladele et al. (2019) for the independent variables and Abdulazeez et al. (2018) for the dependent variable. Statistical tools used in this study are mean and Pearson r. The results of this study show that the level of tax knowledge, tax enforcement efforts, and tax compliance are all very high. In addition, the results indicate a positive significant relationship between tax knowledge and tax compliance and relationship between tax enforcement efforts and tax compliance. Thus, the null hypothesis of the two relationships in this study is rejected. The study suggests considering tax knowledge and tax enforcement efforts to improve tax compliance.